Absolute moral standards and global identity as independent predictors of collective action against global injustice. (December 2015) - Barth, Markus; Jugert, Philipp; Wutzler, Markus; Fritsche, Immo
Abstract: Today's global challenges necessitate the cooperation of the international community. In two studies, this paper investigates global identity and absolute moral standards as two important predictors of solidarity and collective action intentions. In Study 1 ( N = 450), we found evidence for parallel direct effects of global identity and absolute standards on intergroup solidarity and indirectly on collective action intentions. Similar, albeit weaker, effects were found for real behavior (a donation). Study 2 ( N = 124) experimentally manipulated participants' moral standard. Participants in the absolute standard condition were more willing to participate in collective action than participants who were experimentally focused on a gradual standard. Additionally, Study 2 replicated the indirect effects of global identity and absolute moral standards that we found in Study 1. The results show the important role of global identity and absolute moral standards as independent motivators of collective action.